2021
DOI: 10.3389/fcell.2021.648148
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Alleviates the Suppressive Effect of Hypoxanthine on Oocyte Nuclear Maturation and Restores Meiosis via the Melatonin Receptor 1 (MT1)-Mediated Pathway

Abstract: It is well known that hypoxanthine (HX) inhibits nuclear maturation of oocytes by elevating the intracellular cAMP level, while melatonin (MT) is a molecule that reduces cAMP production, which may physiologically antagonize this inhibition and restore the meiosis process. We conducted in vitro and in vivo studies to examine this hypothesis. The results showed that 10–3 M MT potentiated the inhibitory effect of HX on mouse oocyte meiosis by lowering the rate of germinal vesicle breakdown (GVBD) and the first po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Melatonin receptors (MT1 and 2), which couples with inhibitor G-protein (Gi), are identified in oocytes and granulosa cells ( 27, 28 ). The activated Gi inhibits the activation of adenylyl cyclases (ADCYs), resulting in decrease of cAMP (cyclic adenosine monophosphate), which regulates the activation of protein kinase A (PKA) and CREB (cAMP response element-binding protein) ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin receptors (MT1 and 2), which couples with inhibitor G-protein (Gi), are identified in oocytes and granulosa cells ( 27, 28 ). The activated Gi inhibits the activation of adenylyl cyclases (ADCYs), resulting in decrease of cAMP (cyclic adenosine monophosphate), which regulates the activation of protein kinase A (PKA) and CREB (cAMP response element-binding protein) ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the molecular mechanism of melatonin regulating DNA methylation in oocytes is still covered. Melatonin has two receptors, MT1 and MT2, both of which have been identified in oocytes ( 27 ). Melatonin receptors couple with inhibitor G-protein and can regulate gene expression via cAMP/PKA/CREB pathway ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…14 Several studies in other cell systems have shown that melatonin effects are mediated by interaction with the MT1 receptor. 41,42 MT1-melatonin interaction also ameliorates liver injury caused by alcohol gastric perfusion reducing lipid peroxidation through down-regulation of cAMP, but enhanced the activity of AMPK. 41 Moreover, melatonin-MT1 interaction inhibits insulin secretion in rat insulinoma cells and mouse pancreatic islets through decreased phosphorylation of CREB protein.…”
Section: Discussionmentioning
confidence: 96%
“…For IVM, oocytes were cultured in M16 medium (Sigma, M7292) under paraffin oil for 12 h at 37°C in a 5% CO 2 incubator. For melatonin treatment, oocytes were cultured in M16 medium at a final concentration of 1 mM melatonin (Sigma, M5250) in accordance with previous studies (38,39). For IVO, mice injected with PMSG were further injected with 5 IU of human chorionic gonadotropin (hCG) 46 h later.…”
Section: Oocyte Collection and Culturementioning
confidence: 99%